The Effects of Power, Weather, and Mood on Customers’ Impulsive Buying Behavior - Jung, Sang-Uk; Woo, Nayoung (Archives of Business Research, 2021)
In this study, the consumer types were divided into two groups: power and powerless. First, depending on the sense of power, the interaction effect between power and powerless was verified based on two types of weather: sunny and cloudy. Secondly, the purchase intention of luxury goods was examined as a dependent variable and the difference in purchase behavior patterns were observed. Lastly, based on the mood-congruent effect of consumer purchase intentions, it was confirmed that power influences weather, and the weather and mood are influenced by each other, as also manifested in empirical studies. In particular, the power group had a more significant effect than the powerless group, and the positive mood and weather played a big role for consumers’ intention to purchase luxury goods. Therefore, this study can contribute both theoretically and practically to prepare appropriate marketing strategy plans based on weather and consumer roles—power and powerless.